U-shaped association between sleep duration and urinary albumin excretion in Korean adults: 2011-2014 Korea National Health and Nutrition Examination Survey - Yu, Ji Hee; Han, Kyungdo; Kim, Nam Hoon; Yoo, Hye Jin; Seo, Ji A.; Kim, Sin Gon; Choi, Kyung Mook; Baik, Sei Hyun; Kim, Nan Hee (PLOS ONE, 2018)
Although sleep duration has been extensively studied in metabolic diseases, few studies have investigated the impact of sleep duration on chronic kidney disease. The aim of this study was to examine the relationship between sleep duration and albuminuria in the general population. Among 24,948 adults who participated in the 2011–2014 KNHANES, a total of 19,994 subjects were included in this analysis. Subjects were categorized into the following five groups according to self-reported sleep duration: less than 5 h, 6 h, 7 h, 8 h, and more than 9 h. The association between sleep duration and urinary albumin-creatinine ratio (UACR) was examined cross-sectionally. Subjects with both short and long sleep durations were significantly associated with higher UACR levels and higher proportions of patients with microalbuminuria (30–299 mg/g) and macroalbuminuria (≥300 mg/g) compared to those with a sleep duration of 7 hours. The U-shaped association between sleep duration and UACR remained significant even after adjustment for potential confounders, including age, sex, body mass index, smoking, alcohol, education, income, exercise, estimated glomerular filtration rate, diabetes mellitus, hypertension and hypercholesterolemia. The U-shaped association is more evident in the subgroup aged 65 or older, or in female subjects. Our findings suggest that both short and long sleep durations have a U-shaped association with UACR levels in the general population, independent of potential confounders.